AZJATYCKI PRZEŁOM W POZNAŃSKIEJ NEOFILOLOGII ZE SZCZEGÓLNYM UWZGLĘDNIENIEM SINOLOGII - Bańczerowski, Jerzy (Scripta Neophilologica Posnaniensia, 2019)
The initial events accompanying the foundation of sinology at the Adam Mickiewicz University (AMU) in Poznań are called to mind against the background of the Asiatic context. The appearance of east Asian studies at AMU, including Chinese, Japanese, and Korean studies, was a necessary academic enterprise serving the intercultural development of the Faculty of Modern Languages and Literature. In this respect, these studies made this faculty comparable with the corresponding faculties at other universities in Poland. The role of the Institute of Linguistics in this philological breakthrough has been emphasized, and certain personal experiences of the author have been recollected. The proposal concerning the establishment of the Faculty of Asian and African Studiesat AMU has been briefly justified.